?EFFECT OF CALCIUM CHLORIDE IN VAPOUR LIQUID EQUILIBRIA OF THE SYSTEM 1,4 DIOXANE-WATER - SUBBALAH, T.; RAo, B.V. SUBBA (Biological Sciences - PJSIR, 1995)
A precise knowledge of vapour liquid equilibrium data is required in the design of distillation columns. In the present study an attempt is made to find out the effect of calcium chloride on the vapour liquid equilibrium of the system 1,4 dioxane-water at atmospheric pressure of 760 ± 1 rnrn Hg. It was observed that the calcium chloride is helpful in shifting the azeotropic concentration. Linear relationships were developed between the relative volatilities and concentrations of calcium chloride.